Numerical Investigation on the Dynamic Evolution of Intra-Crustal Continental Delamination - Qi, Rui; Liao, Jie; Liu, Xiaohui; Gao, Rui (Frontiers in Earth Science, 2022)
Delamination often occurs in continental regions, through which process the lithospheric mantle detaches from the continental crust and sinks into the underlying asthenospheric mantle. Various modes of continental delamination are proposed, including the typical mode of delamination along the Moho and the newly proposed delamination along the mid-lithospheric discontinuity. Geological and geophysical observations reveal the possibility of an alternative mode of delamination, i.e., intra-crustal continental delamination, which is rarely studied. Using the 2D thermo-mechanical coupled geodynamical models, we systemically study the dynamic evolution of the intra-crustal continental delamination. Model results suggest that the intra-crustal continental delamination develops along the base of the upper crust, promoted by the intra-crustal decoupling, i.e., the mechanical strength decoupling between the upper and lower crust. The three physical parameters, i.e., the upper crustal thickness, the lower crustal rheology, and the initial Moho temperature all affect intra-crustal strength decoupling, and thus influence continental delamination. Combining with geological and geophysical observations, we speculate that intra-crustal continental delamination taking place along the upper and lower crustal interface is a possible way of continental destruction.